Physiological responses of elite Laser sailors to 30 minutes of simulated upwind sailing - Cunnigham, P.; Hale, T. (Journal of Sports Sciences, 2007)
In this study, we tested the hypothesis that elite dinghy sailing is a whole-body, dynamic, repeated-effort sport, and that increased heart rate and oxygen consumption reflect its dynamic element. Six elite male Laser sailors (mean age 19.7 years, s = 1.82; height 1.81 m, s = 0.03; body mass 78.0 kg, s = 4.1) performed a cycle ergometer test to volitional exhaustion to determine peak oxygen uptake (O2peak) and a simulated 30-min upwind leg sail on a specially constructed Laser sailing ergometer. The simulation protocol was based on video analysis of previous Laser World Championships. Expired gases were collected in Douglas bags, heart rate recorded at rest and after every 5 min, and pre- and post-simulation capillary blood samples taken for blood lactate analysis. Results were analysed with a one-way analysis of variance. Mean O2peak was 4.32 l · min-1 (s = 0.16). Mean simulation O2 was 2.51 l · min-1 (s = 0.24) and peaked at 2.58 l · min-1 (s = 0.25) during the 5th minute. Mean simulation heart rate was 156 beats · min-1 (s = 8), peaking during the final minute at 160 beats · min-1 (s = 10). These results suggest that, unlike pseudo-isometric static hiking, elite dinghy sailing demands a substantial proportion (58%O2peak, s = 5.6) of aerobic capacity.